TEACHER ACTIVITIES IN LEARNING THROUGH THE TPACK-BASED PAIKEM GEMBROT METHOD AT SD NEGERI 14 BANDA ACEH - Siti Mayang Sari; Lili Kasmini; Munawar (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Teacher activity requires abilities, skills, creativity, innovation and intellectual intelligence that a teacher must have. Education goal of national has the broadest possible meaning, namely achieving quality education and teaching using learning methods that have meaning and students' learning interests. The learning method that can be implemented in the RI 4.0 era is the PAIKEM GEMBROT method (Active, Innovative, Creative, Effective, Fun, Joyful and High-Weight Learning). Teacher activity in learning that involves students in the implementation of learning requires active and creative thinking by students. The PAIKEM GEMBROT method through TPACK is implemented in elementary school learning to increase students' understanding in the active learning process, teachers are required to be innovative, creative and produce fun learning and provide a happy and meaningful educational atmosphere. This descriptive qualitative research provides information about teachers' activeness in learning through the TPACK-based PAIKEM GEMBROT method to maximize learning well and in a targeted manner according to learning outcomes. Based on the results of interviews and observations at SD Negeri 14 Banda Aceh with outreach activities carried out to provide direction for teachers to improve the quality of learning using the TPACK-based PAIKEM GEMBROT method, producing active, creative, fun and meaningful technology-based learning that can improve student pedagogy. through the implementation of learning content that includes teaching and improving students' ability to reason.